Metabolically engineered Caldicellulosiruptor bescii as a platform for producing acetone and hydrogen from lignocellulose. Issue 12 (24th August 2020) - Straub, Christopher T.; Bing, Ryan G.; Otten, Jonathan K.; Keller, Lisa M.; Zeldes, Benjamin M.; Adams, Michael W. W.; Kelly, Robert M.
Abstract: The production of volatile industrial chemicals utilizing metabolically engineered extreme thermophiles offers the potential for processes with simultaneous fermentation and product separation. An excellent target chemical for such a process is acetone ( T b = 56°C), ideally produced from lignocellulosic biomass. Caldicellulosiruptor bescii ( T opt 78°C), an extremely thermophilic fermentative bacterium naturally capable of deconstructing and fermenting lignocellulose, was metabolically engineered to produce acetone. When the acetone pathway construct was integrated into a parent strain containing the bifunctional alcohol dehydrogenase from Clostridium thermocellum, acetone was produced at 9.1 mM (0.53 g/L), in addition to minimal ethanol 3.3 mM (0.15 g/L), along with net acetate consumption. This demonstrates that C. bescii can be engineered with balanced pathways in which renewable carbohydrate sources are converted to useful metabolites, primarily acetone and H2, without net production of its native fermentation products, acetate and lactate. Abstract : Caldicellulosiruptor bescii, an extremely thermophilic lignocellulose degrading bacterium, was metabolically engineered to produce acetone as its primary fermentation product. The engineered strains fermented microcrystalline cellulose at 70°C, generating acetone and hydrogen. Potential benefits to an industrial process are described and bottlenecks identified for future work.